Hepatitis C virus NS3/4A quasispecies diversity in acute hepatitis C infection in HIV‐1 co‐infected patients. Issue 6 (27th March 2014) - Nevot, M.; Boesecke, C.; Parera, M.; Andrés, C.; Franco, S.; Revollo, B.; Ingiliz, P.; Tural, C.; Clotet, B.; Rockstroh, J. K.; Martinez, M. A.; the NEAT study group
Summary The growing number of cases of acute hepatitis C (AHC) infections among human immunodeficiency virus type 1 (HIV‐1)‐positive men who have sex with men (MSM) in the last 10 years has promoted the search for predictors of AHC clearance as well as for epidemiological networks of viral transmission. We characterized the diversity and catalytic efficiency of HCV NS3/4A protease quasispecies in AHC patients coinfected with HIV‐1. Plasma samples obtained at HCV diagnosis from 18 MSM HIV‐coinfected patients with AHC were studied. Five HCV monoinfected patient samples with AHC were also investigated. An average of 39 clones from each sample was analysed. The catalytic efficiency of the dominant quasispecies (i.e. the most abundant) from each quasispecies was also assayed for mitochondrial antiviral signalling protein (MAVS) cleavage. Phylogenetic analysis identified two clusters of patients with highly related viruses, suggesting a common source of HCV infection. None of the 18 MSM HIV‐coinfected patients spontaneously cleared HCV, although 78% of the treated patients achieved a sustained virological response after early treatment with pegylated interferon (pegIFN) plus ribavirin (RBV). The synonymous‐nonsynonymous (ds/dn) mutation ratio, a marker of selective pressure, was higher in AHC compared to 26 HIV‐1‐infected men with genotype 1a chronic hepatitis C (CHC) (P < 0.0001). NS3/4A proteases from AHC patients also exhibited higher catalytic efficiency compared to CHC patients (P < 0.0001). No differences were found when ds/dn mutation ratios and NS3/4A protease catalytic efficiencies from AHC HIV‐coinfected patients were compared with AHC monoinfected patients. The presence of epidemiological networks of HCV transmission was confirmed among HIV‐1‐positive MSM. In addition, substantial genetic diversity was demonstrated in AHC. NS3/4A protease efficiency cleaving MAVS may be associated with virus transmission and response to pegIFN/RBV treatment.